The Determinants of Regional Income Inequality in Russia : A Quantitative Study - Khazieva, Amaliia (2023)
Addressing regional income inequality is crucial for sustainable economic development, particularly in a vast and resource-rich country like Russia with notable income disparities. This thesis tests two hypotheses: firstly, that regions with initially lower income per capita may catch up economically with higher-income regions, reducing income disparities; and secondly, that higher average income per capita does not necessarily equate to more equitable income distribution as measured by the Gini coefficient. The methodology involves a comprehensive analysis of regional data from 2008 to 2022, focusing on nominal income per capita, the cost of a fixed basket, and the Gini coefficient, employing Beta convergence models. The results indicate a general trend of income beta convergence across most Russian regions, supporting the first hypothesis of income catch-up, but also reveal significant regional variations in the relationship between average income and income distribution, challenging the second hypothesis and highlighting the complex nature of income inequality in Russia.